Sri Lanka Economy In Transition : progress, problems, and prospects - Kelegama, Jayantha B., 1928-2005.; Tennakoon, Ajitha (Colombo : Vijitha Yapa Publications, 2009)
Contributed articles on Sri Lankan economy during post-independence era.
"A tribute to Jayantha Kelegama."
Includes statistical tables.
Includes bibliographical references.
Keywords: Sri Lanka -- Economic conditions -- 20th century; Sri Lanka -- Economic conditions -- 21st century; Sri Lanka -- Economic policy